Enhancing dietary adherence among African-American adolescents: the role of parenting styles and food-related practices - Ardakani, Azam; Monroe-Lord, Lillie; Wakefield, Dorothy; Castor, Chimene (Frontiers in Nutrition, 2024)
Introduction: Parenting styles (PSs) and food-related parenting practices (FPPs) play a crucial role in shaping adolescent eating behavior. This study aimed to investigate the relationship between the different PSs and FPPs of African-American families and the frequency of consumption of MyPlate food items by adolescents based on recommendations from the Dietary Guidelines for Americans (DGA). Methods: This study used a cross-sectional design. Data collection was conducted using Qualtrics through an online survey of 211 African-American parents and their adolescents aged 10-17-year-old. Adolescents completed the Youth and Adolescent Food Frequency Questionnaire to assess their dietary behavior, while parents filled out the survey to identify the degree of PSs (i.e., authoritative, authoritarian, setting rules, and neglecting) and FPPs (i.e., monitoring, reasoning, copying, and modeling). Spearman's rank correlation coefficient, Wilcoxon rank-sum test, and stepwise logistic regression were performed to determine the answers to the research questions. Results: for fruit consumption, authoritative parenting significantly reduced the likelihood of